2014
DOI: 10.3892/br.2014.230
|View full text |Cite
|
Sign up to set email alerts
|

Association between TGFB1 915G/C polymorphism and susceptibility to chronic hepatitis C virus infection: A meta-analysis

Abstract: Abstract. The human transforming growth factor-β1 (TGF-β1) gene, namely TGFB1, contains several single-nucleotide polymorphisms (SNPs) and some of the polymorphic variants were shown to affect the TGF-β1 protein levels. A number of studies reported the association between 915G/C polymorphism and susceptibility to chronic hepatitis C virus (HCV) infection. However, the results were inconsistent. This meta-analysis was conducted to assess the association of TGFB1 915G̸C polymorphism with susceptibility to chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…This mechanism may result in the correlation of the polymorphism of codon 25G/C and chronic HCV infection. However, one previous meta-analysis demonstrated that the polymorphism of TGF-β1 codon 25G/C wasn’t correlated with the chronic HCV infection [31]. In our proposed meta-analysis, the summary results were obtained by pooling the data from the latest and most complete studies and conducting the total analysis, subgroup analyses and the different comparison of controls analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism may result in the correlation of the polymorphism of codon 25G/C and chronic HCV infection. However, one previous meta-analysis demonstrated that the polymorphism of TGF-β1 codon 25G/C wasn’t correlated with the chronic HCV infection [31]. In our proposed meta-analysis, the summary results were obtained by pooling the data from the latest and most complete studies and conducting the total analysis, subgroup analyses and the different comparison of controls analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The action of cytokines can result in anti- or pro-inflammatory effects and growth stimulation or inhibition [ 12 ]. Several studies have shown that the host genetic factor plays a significant role in this immune response and the outcome of HCV infection [ 13 ].…”
Section: Discussionmentioning
confidence: 99%